2022
DOI: 10.3389/fcimb.2022.847846
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Availability of Amino Acids, Proteins, and Iron Impacts Copper Resistance of Aspergillus fumigatus

Abstract: The transition metals iron and copper are required by virtually all organisms but are toxic in excess. Acquisition of both metals and resistance to copper excess have previously been shown to be important for virulence of the most common airborne human mold pathogen, Aspergillus fumigatus. Here we demonstrate that the ambient availability of amino acids and proteins increases the copper resistance of A. fumigatus wild type and particularly of the ΔcrpA mutant that lacks export-mediated copper detoxification. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Multiple “favorable amino acids” were examined in Figure b,c and Supplementary Figure 23, and their significant enrichment suggested that metabolism of intermediates (3-phosphoglycerate, pyruvate, phosphoenolpyruvate, erythrose-4-phosphate, 2-oxoglutarate and oxaloacetate) from glycolysis, the citric acid cycle, and the pentose phosphate pathway were upregulated (especially in shrub soils with superior resistance and resilience compared to their grass counterparts) (Supplementary Table 14). Specifically, for amino acids negatively correlated with enzymes, Met was not considered due to the low detection limit, whereas the increased His in shrub soil may be due to the ambient availability (highest protecting activity compared to other amino acids) of His increasing cellular tolerance to PSMPs . These results further emphasize the advantages of shrub soils in enhancing the metabolic effects.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Multiple “favorable amino acids” were examined in Figure b,c and Supplementary Figure 23, and their significant enrichment suggested that metabolism of intermediates (3-phosphoglycerate, pyruvate, phosphoenolpyruvate, erythrose-4-phosphate, 2-oxoglutarate and oxaloacetate) from glycolysis, the citric acid cycle, and the pentose phosphate pathway were upregulated (especially in shrub soils with superior resistance and resilience compared to their grass counterparts) (Supplementary Table 14). Specifically, for amino acids negatively correlated with enzymes, Met was not considered due to the low detection limit, whereas the increased His in shrub soil may be due to the ambient availability (highest protecting activity compared to other amino acids) of His increasing cellular tolerance to PSMPs . These results further emphasize the advantages of shrub soils in enhancing the metabolic effects.…”
Section: Resultsmentioning
confidence: 80%
“…82 Specifically, for amino acids negatively correlated with enzymes, Met was not considered due to the low detection limit, whereas the increased His in shrub soil may be due to the ambient availability (highest protecting activity compared to other amino acids) of His increasing cellular tolerance to PSMPs. 83 These results further emphasize the advantages of shrub soils in enhancing the metabolic effects.…”
Section: Psmp-facilitated Soil Carbon Mineralization Wasmentioning
confidence: 72%
“…Emerging data show that there is a tight association between the metabolism of different transition metals in fungi, in addition to the copper dependence of iron uptake via the reductive iron assimilation pathway, which has been observed in several fungi ( 20 , 25 , 33 ). It has also been shown that an increase in intracellular copper levels can elevate the iron content in A. fumigatus cells ( 34 ). Iron availability also regulates zinc metabolism mediated by the transcription factor ZafA ( 35 ), and in line with this, iron starvation has been shown to upregulate the vacuolar zinc transporter ZrcA (important in removing excess zinc from cytosol) and downregulate the zinc importer ZrpB in A. fumigatus ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages secrete Cu 2+ into the phagosomes to kill the ingested microbes ( 13 , 14 ). Moreover, iron-limited conditions of phagosomes and superoxide anion secreted into the phagosomes enhance copper toxicity further ( 34 ). Microbes may also suffer from iron/zinc overload when they escape from phagosomes to the cytosol ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation